United Republic of Tanzania : Fourth Review Under the Policy Support Instrument; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for United Republic of Tanzania. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the Fourth Review under the Policy Support Instrument (PSI) for the United Republic of Tanzania. By October 2008, inflation had risen to 11.8 percent mainly reflecting the surge in global food and fuel prices, but is expected to begin to recede. Poverty indicators have improved, although progress is slower than hoped in some areas. The outlook for 2009 is for continued robust growth, but the current global environment poses serious downside risks. Despite some slippages, there has been good progress on the PSI-supported program.